Magnetic resonance diffusion metrics indexing high focal cellularity and sharp transition at the tumour boundary predict poor outcome in glioblastoma multiforme. Issue 12 (December 2015) - Jamjoom, A.A.B.; Rodriguez, D.; Rajeb, A.T.; Manita, M.A.; Shah, K.A.; Auer, D.P.
Abstract : Aim: To investigate the prognostic power of intra-tumoural and gradient magnetic resonance imaging (MRI) diffusion metrics in patients with glioblastoma multiforme (GBM). Materials and methods: Forty-six consecutive patients with histologically confirmed GBM who had undergone preoperative diffusion tensor imaging at 3 T were included. Mean diffusivity (MD) and MD gradient maps were computed. Regions of interest were analysed to determine the minimum MD within the enhancing tumour (minMD). MD gradients were calculated along the enhancing tumour boundary and subjected to histogram analysis. Overall survival (OS) and time to progression (TTP) were derived and survival analysis was undertaken. Results: There were 31 deaths and 37 patients progressed during the study period. Multivariate survival analysis, controlling for treatment and gender, showed that minMD values<6.1×10 −4 mm 2 /s predicted shorter OS (hazard ratio [HR]=2.82, 1.25–6.34; p =0.012) and TTP (HR=5.43, 1.96–15.05; p =0.001). Higher MD gradient values of the tumour boundary predicted shorter survival: MD gradient values >4.7×10 −5 mm 2 /s (10 th centile) had a significantly shorter OS with a HR of 0.43 (0.19–0.96; p =0.04). Similarly, a value above 1.4×10 −4 mm 2 /s (75 th centile) was a significant predictor for shorter OS (HR=0.39, 0.17–0.89; p =0.03). Conclusions: Lower minMD and higher MD gradient values for the 10 th and 75 th percentile of the tumour boundary demonstrated prognostic value in preoperative GBM. This suggests that MRI diffusion metrics indicative of higher focal cellularity and steeper transition from high cellular tumour edge to low cellular oedema define more aggressive glioblastoma subtypes with a poorer prognosis. Highlights: A novel approach to examine the whole tumour boundary of GBMs using MR diffusion histogram analysis is demonstrated. Greater cellularity difference between the tumor edge and surrounding tissue were associated with shorter overall survival. High intra-tumoral cellularity as indexed by low minimum mean diffusivity was associated with poorer prognosis.